Cultural memory and place identity: creating place experience - Raadik-Cottrell, Jana, author; Donnelly, Maureen P., advisor; Vaske, Jerry J., 1951-, committee member; Dickinson, Greg, committee member; Taylor, Peter, committee member (Colorado State University. Libraries, 2010)
Studying landscapes anchored in human life, with natural and cultural components interwoven as one fabric, embracing the political and ideological aspects, helps to understand the role of our everyday landscapes in tourism. Tourism, the travel between places and touring of landscapes, is essential to the identity process of both travelers and places. The notions of "home" and "elsewhere," "us" and "them" are constructed through mobility, motility (potentials of mobility) and migration. The scope and scale of mobility and motility has changed in a postmodern world through the intensity in time-space expansion/ contraction. Contemporary European society is fractured in a struggle between conflicts of identity (former Eastern Europe). Renegotiations of past and present, integration and diversity are especially acute after the collapse of the Soviet empire and ongoing enlargement of the European Union. Identity and culture are elastic concepts, involving conscious and unconscious processes through which places are lived and made while giving meaning to the lives of the people involved. Communication of those meanings is essential to each individual in this process and to others beyond the actual lived place. The meaning attached to landscapes is negotiable due to competing social actors involved in a continuous interpretation and variability offered across cultural, historical, individual and situational aspects. This case study examines the dynamic between real landscapes, their representations and negotiations of identity under the umbrella of a stabilizing past among foreign and domestic visitors to Saare County on Saaremaa Island in Estonia. The disruptive societal changes, which occurred in recent decades with the collapse of the Soviet regime, guide discussion of interactions of place, identity, landscape and memory, as well as the role of tourism. The central aim of this dissertation is to explore the role of past through individual and collective memory in multifaceted negotiations of place identity and place experience. Huff's (2008) model of landscape, place and identity combined with memory and tourism was used to guide this investigation. Data were collected in three phases: content analysis of online news article debate about the potential bridge connecting Saaremaa Island to mainland Estonia (n=123), onsite tourist survey of visitors to the island (n=487), and in-depth interviews with 16 visitors drawn from the survey sample. Narrative and discourse analyses were supplemented by a multiple/logistic regression of survey data in a mixed methods approach. Results imply that pro-anti bridge sentiment exists among Estonians and foreigners based on socio-cultural and political contexts in a post Soviet society. Memory, well-being, and aesthetics of place with nationality, and education are predictors of perceived effects of environmental changes and effects of a bridge to mainland on future holiday experiences to Saaremaa Island. Past memories from ideological images of place and memories of places elsewhere were intertwined into bodily perceptions of place, yet resulted in somewhat contradictory statements. Evaluation of changes in landscapes correlated with perceived identities of place and self, and reflected upon readings of home. Historical aspects of place were deemed an important part of place experience. Respondents without prior knowledge or experience similar to the socio-cultural, economic and political context in Estonia were inclined to identify place based on comparisons of home place from their own residency and past memories from places traveled elsewhere. Outcomes suggest a dialogue for further sense of place research in tourism for the marketing and management of sustainable tourism development in general and for island destinations in particular.
Department Head: Michael J. Manfredo.